Development and characterization of hydroxyapatite and multiwall carbon nanotubes reinforced polypropylene biocomposites - Abdel Rahman Elmofty; Marwa E. Abdel Aziz; Mahmoud Tash; Shimaa El-Hadad (Scientific Reports)
Abstract Two groups of Polypropylene/hydroxyapatite nanocomposites (PP/nHA) were fabricated by melt blending of PP with (5, 10, and 20 wt%) of hydroxyapatite nanoparticles nHA with two different sizes (~ 40 and 90 nm). The nanocomposites were prepared without and with the addition of 0.3 wt% of multiwall carbon nanotubes (MWCNTs). The effect of HA size and content as well as the addition of MWCNTs on the structure, thermal and mechanical properties of the prepared composites was investigated. All the samples were immersed in simulated body fluid (SBF) to compare their ability to precipitate HA from SBF. Scanning electron microscope (SEM), X-ray diffraction analysis (XRD), thermogravimetric analysis (TGA), and tensile strength tests were used for the investigation. XRD patterns reveal that incorporating nHA particles and/or MWCNT into the polymer matrix does not cause any structural change to the PP crystalline lattice. SEM shows a significant improvement in the dispersion of nHA particles along PP matrix with a smoother surface morphology by the addition of MWCNTs. Based on the thermal studies, both nHA particles and MWCNTS were known to enhance the thermal stability of the prepared composites. The tensile strength of PP increased by 20% for PP-5% (90 nm) HA-MWCNTs composites and 44% for PP-5% (40 nm) HA-MWCNTs composites. Furthermore, in vitro studies reveal the apatite-forming ability on the surface of the prepared composites especially those prepared using MWCNTs.